Experimental testing and numerical modelling of a large-scale modular cellular structural steel and composite sandwich decking flooring system in fire - Claasen, Jaleel Joseph (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.